Longitudinal Reciprocal Relationships Between Quality of Life and Coping Strategies Among Women with Breast Cancer. Issue 5 (8th June 2016) - Paek, Min-So; Ip, Edward H.; Levine, Beverly; Avis, Nancy E.
Abstract: Background: Research on quality of life (QoL) among women with breast cancer has often examined the impact of coping strategies on QoL. However, the transactional model of stress and coping would argue that QoL can impact coping. This reciprocal relationship between QoL and coping has been inadequately studied. Purpose: This study examined reciprocal relationships over 18 months between QoL and coping (positive and negative coping) among women with breast cancer. Methods: Three-wave cross-lagged structural equation modelling (SEM) analysis was used over three timepoints post-diagnosis (T1–T3; N  = 637, 577, 553, respectively). Results: SEM results revealed a significant reciprocal relationship between negative coping and QoL, indicating that negative coping predicted subsequent QoL, which in turn predicted later negative coping. Although QoL at cancer diagnosis predicted subsequent positive coping, we did not find a reciprocal relation between QoL and positive coping. Conclusion: Findings expand our knowledge of the relation between QoL and coping by suggesting the reciprocal relationship between negative coping and QoL among women with breast cancer.